A Study on the Linguistic Processes of the Lutheran Reformation and Northern Europe - Buožytė, Eleonora (Literatūra, 2019)
Kauko, Mikko, Miika Norro, Kirsi-Maria Nummila, Tanja Toropainen & Tuomo Fonsén, eds. 2019. Languages in the Lutheran Reformation. Textual Networks and the Spread of Ideas. Amsterdam: Amsterdam University Press, 303 p. ISBN 978 94 6298 155 3.